Metastatic extragenital neoplasms to the uterus: a clinicopathologic study of four cases. (1st January 2006) - Giordano, G.; Gnetti, L.; Ricci, R.; Merisio, C.; Melpignano, M.
Abstract : The aim of this study was to elucidate the clinicopathologic features, the differential diagnostic problems, and the prognostic consequences of patients with metastatic extragenital malignancies to uterus. The patients with metastatic extragenital malignancies to the uterus were evaluated. We considered the metastases in non–genital tract organs at diagnosis of primary neoplasm, the distribution of the metastases in the uterus, and the presence of concomitant metastases in other genital and non–genital tract organs. There were four cases of metastatic extragenital malignancies to the uterus. The breast was the most frequent primary site (two cases: 50%). The other two primary tumors were adenocarcinoma of the cecum and malignant melanoma of the skin. The diagnosis was facilitated by clinical history, revealing the previous primary neoplasm, and by specific immunohistochemical study. Almost all the patients died from disseminated disease. Thus, the prognosis of metastatic extragenital malignancies to the uterus alone or simultaneously to the uterus and other organs of the genital tract is poor. Thus, the metastases to the uterus and to other organs of the genital tract can be considered a preterminal event.